ANALYSIS ON THE INFLUENCE OF THE SPIRAL RISE ANGLE OF SHEARER DRUM ON THE CUTTING PERFORMANCE - WANG Hui; SONG YuNing (Jixie qiangdu)
In this paper,the influence of the spiral angle of shearer drum on the cutting performance is studied in this paper.The calculating formula of the drum helical blade coal throwing force and loading quantity theory.According to the theoretical analysis,it is known that the axial force of the blade is inversely proportional to the helix angle and the rotation speed of the roller,which is proportional to the speed of the traction.The theory of the loading quantity and the roller speed is proportional to,and with the increase of spiral angle of parabola increased first and then decreased.Using ADAMS software to simulate the variation of axial force and cutting power of shearer drum in different spiral angle,and the results are consistent with the theoretical analysis.In the design of the shearer drum,the influence of the spiral blade on the cutting performance of the shearer should be considered,so that the utility and economic benefit of the shearer can be optimized.